A Method for Computing Optimal Decision Rules for a Competitive Firm - O'Connor, J. F. (Econometrica, 1978)
[This paper deals with the problem of computing optimal strategies in a model of intertemporal choice under uncertainty for a competitive firm. The paper presents a method for computing the optimal strategies for (i) investment, (ii) production, (iii) financing, and (iv) consumption or dividends when (i) the entrepreneur's utility function displays constant absolute risk aversion, (ii) the production technology is certain and of the activity analysis variety, and (iii) prices are uncertain and serially independent. It is shown that the task of finding the optimal investment and production strategies reduces to a concave programming problem while the optimal financing and consumption strategies can be computed by analytical methods after the investment and production strategies are obtained. When prices are normally distributed, the optimal production and investment strategies can be found by means of quadratic programming.]